U.S.-Czech ballistic missile defense cooperation: Lessons learned and way forward for others. Issue 3 (3rd May 2020) - Dodge, Michaela
Abstract: The article identifies factors that impacted ballistic missile defense cooperation between the Czech Republic and the United States after 2002 when the United States withdrew from the Anti-Ballistic Missile Treaty. It draws insights regarding a broader question of why countries of disproportionate capabilities cooperate on defense-related matters despite gaining asymmetric benefits. How does such cooperation occur is relevant for the United States as it cooperates on ballistic missile defense with about 20 countries worldwide. The article makes contributions to literature on alliance politics and management. The case study illustrates that defense cooperation between two countries can result in similar outcomes as if their threat perceptions were the same even when they differ and highlights a critical role and importance of domestic politics on defense negotiations. The article offers several actionable policy recommendations.